Vanadium and its complexes: The renewed interest in its biochemistry - Pepato, Maria T. [UNESP]; Khalil, Najeh M. [UNESP]; Giocondo, Maísa P. [UNESP]; Brunetti, Iguatemy L. [UNESP] (My University, 2008)
The field of bioinorganic chemistry, which explores the interactions between inorganic compounds and biological systems, has been growing rapidly in the last few years. Various elements and their compounds have attracted great interest, particularly vanadium. In this article we review the effect of vanadium and its complexes on diabetes mellitus.
Keywords: Complex [(ethylenediaminete-traacetato) bis(oxovanadium(IV)]; Complex [bis(morpholine-4-carbodithiolate)oxovanadium(IV)]; Diabetes mellitus; Toxicity; Vanadium